Post-earthquake functionality of highway overpass bridges. - Mackie, K. R. (Earthquake engineering & structural dynamics.)
Bridges are crucial to the transportation network in a region struck by an earthquake. Collapse of a bridge determines if a road is passable. Ability of a bridge to carry traffic load after an earthquake determines the weight and speed of vehicles that can cross it. Extent of system and component structural damage in bridges determines the cost and time required for repair. Today, post-earthquake bridge evaluation is qualitative rather than quantitative. The research presented in this paper aims to provide a quantitative engineering basis for quick and reliable evaluation of the ability of a typical highway overpass bridge to function after an earthquake. The Pacific Earthquake Engineering Research (PEER) Center's probabilistic performance-based evaluation approach provides the framework for post-earthquake bridge evaluation. An analytical study was performed that linked engineering demand parameters to earthquake intensity measures. The PEER structural performance database and reliability analysis tools were then used to link demand parameters to damage measures. Finally, decision variables were developed to describe three limit states, repair cost, traffic function, and collapse, in terms of induced damage. This paper presents the analytical models used to evaluate post-earthquake bridge function, decision variables and their correlation to the considered limit states, and fragility curves that represent the probability of exceeding a bridge function limit state given an earthquake intensity.